ANALISIS PENGARUH PENGETAHUAN UMUM, TINGKAT EKONOMI, DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN PBB MASYARAKAT DESA DAN KOTA DENGAN VARIABEL MODERATING KONTROL PETUGAS DESA/KELURAHAN (STUDI KASUS PADA KABUPATEN DEMAK) - Carola Ditta Surya Putri; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2013)
Land and Building Tax (PBB) is one of the regional revenue that are important because it is used for regional development. In addition, Land and Building Tax (PBB) has the largest taxpayers than the other tax, and revenues from year to year increased by a greater percentage than the other taxes. Therefore, the Tax Compliance from the PBB’s tax payers is important in its contribution to the development and prosperity of the region. This study is conducted to determine the factors that may affect the Land and Building Tax Compliance in Demak and to compare the Tax Compliance from Urban taxpayers and Rural taxpayers. The tax payer’s compliance is influenced by factors General Knowledge, Economic Level, and Tax Knowledge which is moderating by the Control Officer Rural/Urban Village.All variables were measured using a 5-point Likert scale questionnaire. Population of this study is taken from Demak Regency and samples were taken by purposive sampling method. The method of testing is done by linear regression analysis and t-test-test is processed by SPSS version 21.The results have shown that the common knowledge and tax knowledge is not a significant influence on the Tax Compliance. Whereas, the economy level can provide a significant and negative impact on the Tax Compliance. On the other hand, the Control Officer Village / Village can strengthen the influence of General Knowledge and Economic Level of the Tax Compliance. However, the control officer actually weaken the influence of the Tax Compliance and Tax Knowledge.